Examen Especial a la Cuenta de Inversiones en Asociadas, Subsidiarias y Negocios en Conjunto, C.A. Ecuatoriana de Cerámica de la ciudad de Riobamba, periodo 2021. - Cali Jimenez, Adriana Lizbeth (2023)
The work titled "Special Examination of Investments in Associates, Subsidiaries, and Joint Ventures, C.A. Ecuatoriana de Cerámica, Riobamba City, 2021 period" aimed to analyze and evaluate the investments made by the company during the mentioned period, determining the accuracy and reliability of the financial information and identifying possible deficiencies in the implemented internal controls. A mixed approach was used, where qualitative analysis allowed for an understanding of the specific characteristics of the investments and their financial and operational implications. In contrast, the quantitative approach involved the study of financial and accounting data related to acquisitions. During the investigation, deficiencies in implementing internal controls were found, including errors in the accounting records, lack of supporting documentation, and failure to update investment movements. These deficiencies compromise the accuracy and reliability of financial information and can hurt decision-making. The company strengthens internal controls related to investments by implementing adequate documentation procedures, regularly reviewing accounting records, and keeping investment movements updated. In conclusion, the special examination conducted on account of investments in associates, subsidiaries, and joint ventures of C.A. Ecuatoriana de Cerámica during the 2021 period revealed deficiencies in the company's internal controls, compromising the accuracy and reliability of the financial information related to these investments.